Features of deontology in oncology - Asatulaev, A.F.; Turazoda, M.U. (Science and Education, 2023)
The article analyzes the main points and features of deontology in oncological practice. The oncologist in his practice meets with the issues raised on a daily basis. Examples are also given from practical situations that probably every oncologist has encountered. The work emphasizesAn important feature of deontology is the need to constantly fight against the widespread belief that malignant neoplasms are incurable.